Analisis Pertimbangan Putusan Hakim Pengadilan Agama Wonosari Tentang Penetapan Perwalian Orang Tua Kandung - Faqih Thariqu Billah (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Case Decision Nomor 39/Pdt.P/2023/PA.Wno is the decision of the Wonosari Religious Court which granted the parents' (mother's) request for guardianship of their biological child. Even though Article Pasal 47 Undang-undang Nomor 16 Tahun 2019 tentang Perkawinan, explains that children are under 18 years old and have never been married. So his guardianship power is under the responsibility of his parents. Parents as guardians represent all legal actions related to their children, both inside and outside the court. Biological parents automatically become guardians of their children without needing to determine guardianship in a religious court. It's just a civil practice that occurs in the field, the Land Deed Making Officer (PPAT) requires parents to first make a guardianship determination with the religious court, when they want to take care of their child's inherited land. Based on the description of the context of this research, there is a gap between the law (das sollen) and the legal reality that occurs (das sein).